Web-Based Business Planning System (Analysis and Forecast) / How Men Mee - How, Men Mee (2002)
Planning is an important activity. It requires making estimates about future needs and developments, which are difficult to predict and control. So, Web-Based Business Planning System (BPS) explains, more in detail, the fundamental of planning and how it is used in decision making, capital project feasibility studies, and planning the future of a business. Web-Based Business Planning System (BPS) is a centralized channel on the web to allow user (manager or sales person) to retrieve or upload information through this system anytime and anyway as long as they connect to the Internet. This system allow user to view or update their sales data, do analysis or forecast and view the analysis and forecast report. Web-Based Business Planning System (BPS) is capable of improving the quality and outcome of analysis and forecast by ensuring that accurate, fast and timely information is made accessible to appropriate personnel at all level. In addition, Web-Based Business Planning System (BPS) inform the user about the report via PivotTable and PivotChart. Methodology that I was selected to develop this Web-Based Business Planning System (BPS) is Waterfall model with prototyping. The flexible of this methodology made me easy to development the system and reduces the risk involved. The development tool that I go to use is Ms Visual InterDev, whereas the web server was Internet Information Server 5.0 with back-end database Ms SQL server 2000 and OLAP. Both server were deployed on Windows 2000 Server. The system design chapter will illustrate how the entire system works. Many problem were encountered during the process of development this system. Many approaches were used to solve the entire problem to perform a good Web-Based Business Planning System (BPS). Besides, also discuss about the strength, limitation and the future enhancement of the system.